Peran Jabhat Al-Nusra dalam Memberikan Tantangan terhadap Kebijakan Amerika Serikat Mendukung Kelompok Oposisi pada Konflik Bersenjata di Suriah - Kamrullah, Muhammad Rizky Nur (UI Scholars Hub, 2017)
The role of non-state actor in contemporary world politics is increasingly important. After 9/11, scholars of security study and security practitioners begin to concern about the non-state actors which usually called as terrorist group or terrorist organization. The use of violence by those actors makes them can be classified as Violent Non-state Actor (VNSA). It cannot be denied that VNSAs activity can affect the state security policy and provoke state to war against them. Therefore, this paper will examine Jabhat al-Nusra—as an actor with tied to Al-Qaeda—involvement in the Syrian armed conflict, as a phenomenon that illustrates the role and influence of VNSA in affecting state behavior. This paper will try to show any factors that allow Jabhat al Nusra capabilities to be an important actor on the conflict dynamics. This paper argues that VNSA global politics potential character within Jabhat al-Nusra, is the factor that make them can grow to be a main actor in the rebel ranks and affecting the United States policy in the Syrian armed conflict.